Industrial Training Report: Portal Services Division Group IT- Customer Interaction Telekom Malaysia Berhad / Norakma Mokhtar - Mokhtar, Norakma (Faculty of Information Management, 2017)
This report entails the experience of mine throughout industrial training, the background of Telekom Malaysia Berhad. Portal is a useful medium in the organization since it can help in the process of update the data and effective gathering information. Portal Customer Interaction (Cl) in which the specific name is "INTERAKSI" have been established in this department in order to improve the management of information and avoid from mishandling of information retrieving. The main objective of this portal development is to help and assist the department of Customer Interaction (Cl) in order for them to have their own portal for manage daily activity in the organization and to ensure all task from paper based to be transform into digital form in which it can make the information management become more manageable and systematic. In additional, the design of portal are been used medium such as WordPress and XAMPP server to manage the database. The development of the portal is to ensure the department can easily manage and take these advantages to manage the information effectively and wisely.